Plasma levels of antimicrobial peptide LL-37 as a biomarker of sleep quality in patients with obstructive sleep apnea: A clinical observational study - Takayuki Yamaguchi; Keisuke Hosokawa; Takenori Mineta; Rie Hosokawa; Shiho Odawara; Rie Chiba; Kazue Asanuma; Setsuko Toyomaki; Mitsuho Sato; Fumiaki Takahashi; Shigeru Sakurai; Kazuhiro Takahashi; et al. (PLOS One, 2026)
Objectives Obstructive sleep apnea (OSA) is characterized by systemic inflammation, intermittent hypoxemia, and immune dysregulation and has been associated with increased susceptibility to viral infections. In this study, we aimed to evaluate plasma concentrations of the antimicrobial peptide cathelicidin LL-37 (pLL-37) in individuals with OSA. Methods The associations between pLL-37 levels, demographic characteristics, and polysomnographic (PSG) parameters were assessed in 58 individuals with OSA and 20 healthy controls. Participants were stratified into two groups stratified by apnea–hypopnea index (AHI): AHI < 15 and AHI ≥ 15. Multiple regression analysis was conducted to identify independent predictors of pLL-37. Results Significant negative correlations were observed between pLL-37 levels and age, percentage of Stage N1 sleep based on PSG data (%Stage N1), arousal index, AHI, and oxygen desaturation index. Conversely, significant positive correlations were identified between pLL-37 levels and %Stage N3, percentage of rapid eye movement sleep (%Stage REM), mean percentage of peripheral oxygen saturation (%SpO 2 mean), and %SpO 2 minimum. Mean pLL-37 level was significantly higher in the AHI < 15 group (75.3 ± 29.3 ng/L) than in the AHI ≥ 15 group (47.1 ± 18.3 ng/L). Multiple regression analysis identified %Stage N1 as an independent factor associated with pLL-37. Conclusions pLL-37 levels were significantly reduced in individuals with severe OSA than in healthy controls. %Stage N1 was independently associated with pLL-37 levels, suggesting a decline with worsening oxygen desaturation. These findings suggest pLL-37 may serve as a biomarker for sleep quality and the severity of impaired oxygenation during sleep with implications for immune vulnerability and infection risk in OSA.